The Analysis Study of The Effect of Intraosseus Infiltration of Platelet Rich Plasma for Knee Osteoarthritis : A Comprehensive Systematic Review - Gede, Odi Bayu Dharma Perkasa; Christian, Stedi Adnyana (The International Journal of Medical Science and Health Research, 2024)
Background: Knee osteoarthritis (KOA) is an active, heterogeneous, and low-grade inflammatory condition leading to functional disability and pain. The aim: The aim of this study to show about the effect of intraosseus infiltration of platelet rich plasma for knee osteorthritis. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Intraosseous (IO) PRP injections to target subchondral bone can provide a more comprehensive treatment by stimulating biological processes that lead to an environment primed for regeneration. Restoring joint homeostasis also influences the behaviour of MSCs that coordinate bone remodelling of the subchondral bone.